Atypical Hereditary Sensory and Autonomic Neuropathy Type IV With Neither Mental Retardation Nor Pain Insensitivity. (December 2013) - Jung, Chae Lim; Ki, Chang-Seok; Kim, Byoung Joon; Lee, Jong-Hyuck; Sung, Ki-Sun; Kim, Jong-Won; Park, Youn-Soo
Hereditary sensory and autonomic neuropathy type IV is an autosomal recessive disorder characterized by severe mental retardation and self-mutilation-related complications. Recently, we investigated a 16-year-old Korean boy with normal intelligence. He had preserved pain sensation but was suspected of having hereditary sensory and autonomic neuropathy type IV because of the recurrent bone fractures and painless joint destruction in the absence of any predisposing medical conditions. Genetic analysis of the NTRK1 gene revealed compound heterozygous mutations including c.851-33T>A and c.2303C>T (p.Pro768Leu) in the NTRK1 gene. The p.Pro768Leu mutation has been identified in 2 Japanese patients with a mild phenotype. Therefore, although it is rare, hereditary sensory and autonomic neuropathy type IV should be considered in patients with recurrent bone fractures and painless joint destruction who do not have any predisposing conditions even when they do not have typical clinical features such as mental retardation or pain insensitivity.